The Role of Loneliness as a Mediator between Emotional Dysregulation and Doomscrolling in College Students - Safaria, Triantoro; Saputra, Bayu Aji (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2025)
This study aimed to investigate the role of loneliness as a mediator of the relationship between emotional dysregulation and doomscrolling among college students in Yogyakarta. The cross-sectional quantitative design included 200 active college students recruited through random sampling. Participants completed the Emotion Regulation Difficulties Scale (DERS), the De Jong Gierveld Loneliness Scale (DJGLS), and the Doomscrolling Scale (DS). Mediation analysis was conducted using bootstrapping-based analysis, Hayes PROCESS/ModMed on Jamovi. The results showed that emotional dysregulation directly predicted doomscrolling (β = .196, p = .020) and loneliness (β = .511, p < .001). Loneliness also increased doomscrolling (β = .549; p < .001) and partially mediated the relationship (β = .280; p < .001), with a total effect of β = .477 and a mediation proportion of 58.8%. These findings outlined the importance of emotion regulation interventions and social connection, strengthening programs on campus to reduce doomscrolling.